Gestation-Specific Vital Sign Reference Ranges in Pregnancy - Green, Lauren J.; Mackillop, Lucy H.; Salvi, Dario; Pullon, Rebecca; Loerup, Lise; Tarassenko, Lionel; Mossop, Jude; Edwards, Clare; Gerry, Stephen; Birks, Jacqueline; Gauntlett, Rupert; Harding, Kate; et al. (Obstetrics and gynecology (New York. 1953), 2020)
OBJECTIVE:To estimate normal ranges for maternal vital signs throughout pregnancy, which have not been well defined in a large contemporary population. METHODS:We conducted a three-center, prospective, longitudinal cohort study in the United Kingdom from August 2012 to September 2017. We recruited women at less than 20 weeks of gestation without significant comorbidities with accurately dated singleton pregnancies. We measured participantsʼ blood pressure (BP), heart rate, respiratory rate, oxygen saturation and temperature following standardized operating procedures at 4–6 weekly intervals throughout pregnancy. RESULTS:We screened 4,279 pregnant women, 1,041 met eligibility criteria and chose to take part. Systolic and diastolic BP decreased slightly from 12 weeks of gestationmedian or 50th centile (3rd–97th centile) 114 (95–138); 70 (56–87) mm Hg to reach minimums of 113 (95–136); 69 (55–86) mm Hg at 18.6 and 19.2 weeks of gestation, respectively, a change (95% CI) of −1.0 (−2 to 0); −1 (−2 to −1) mm Hg. Systolic and diastolic BP then rose to a maximum median (3rd–97th centile) of 121 (102–144); 78 (62–95) mm Hg at 40 weeks of gestation, a difference (95% CI) of 7 (6–9) and9 (8–10) mm Hg, respectively. The median (3rd–97th centile) heart rate was lowest at 12 weeks of gestation82 (63–105) beats per minute (bpm), rising progressively to a maximum of 91 (68–115) bpm at 34.1 weeks. SpO2 decreased from 12 weeks of gestationmedian (3–97 centile) 98% (94–99%) to 97% (93–99%) at 40 weeks. The median (3–97 centile) respiratory rate at 12 weeks of gestation was 15 (9–22), which did not change with gestation. The median (3–97 centile) temperature at 12 weeks of gestation was 36.7 (35.6–37.5)°C, decreasing to a minimum of 36.5 (35.3–37.3)°C at 33.4 weeks. CONCLUSION:We present widely relevant, gestation-specific reference ranges for detecting abnormal BP, heart rate, respiratory rate, oxygen saturation and temperature during pregnancy. Our findings refute the existence of a clinically significant BP drop from 12 weeks of gestation. CLINICAL TRIAL REGISTRATION:ISRCTN, ISRCTN10838017.